The Senses of Agency and Ownership: A Review - Braun, Niclas; Debener, Stefan; Spychala, Nadine; Bongartz, Edith; Sörös, Peter; Müller, Helge H. O.; Philipsen, Alexandra (Frontiers in Psychology, 2018)
Usually, we do not question that we possess a body and act upon the world. This pre-reflective awareness of being a bodily and agentive self can, however, be disrupted by different clinical conditions. Whereas sense of ownership (SoO) describes the feeling of mineness towards one’s own body parts, feelings or thoughts, sense of agency (SoA) refers to the experience of initiating and controlling an action. Although SoA and SoO naturally coincide, both experiences can also be made in isolation. By using many different experimental paradigms, both experiences have been extensively studied over the last years. This review introduces both concepts, with a special focus also onto their interplay. First, current experimental paradigms, results and neurocognitive theories about both concepts will be presented and then their clinical and therapeutic relevance is discussed.